Tourism Management System in Mongolia: the Case of Gorkhi-Terelj National Park - Nergui ERDENEBAT; Yungnane YANG (Smart Cities and Regional Development Journal)
International tourism in Mongolia is in modern term still in its infancy. The first international visitors arrived in 1994, when visas were finally available to international tourists. For all its socialist period, from 1924 until 1992, Mongolia was closed to the outside world. Today Mongolia is, measured by Gross Domestic Product (GDP), one of the poorest nations on earth. The primary foreign exchange earner of Mongolia is the export of minerals. Tourism is increasingly important to the national economy, providing not only hard currency earnings but also desperately needed employment. Stated government policy is the future development of tourism, especially the increase in foreign visitors and the contribution tourism makes to the national economy. Tourism sector in Mongolia is strongly characterized by lack of skilled staff at different levels, affected also by high seasonality of Mongolian tourism sector. Lack of knowledge and skills is a problem that goes throughout the whole tourism sector, from the management level, to the operational staff. Training opportunities in Mongolian tourism sector are limited also by lack of professional training institutions with training programs prepared on the basis of existing training needs. The staff cannot satisfy tourists needs if there is no or bad understanding between them. Goods and services will be improved with skilled labors. This research purpose is to investigate and determine the effectiveness of tourism management system of Mongolia via the review of Gorkhi-Terelj National Park. Tourism management system of Mongolia is examined with three key variables which are: information, resource management, inter-organizational collaboration. In-depth interviews with 4 policy stakeholders with different backgrounds serve as the research method. To fulfill the objectives of this article, the researcher selected people who are tour company director and employees of Ministry of Environment and Tourism.